ETHNO-NATIONAL ASPECTS OF THE SECOND RUSSIAN OCCUPATION TERNOPIL REGION DURING THE FIRST WORLD WAR (1916-1917 YEARS) - Лазарович, М. В.; Лазарович, Н. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Highlights events related to the Russian conquest of Ternopil during World War I. The paper highlights the national policy of the occupation administration in relation to the Ukrainians and some other ethnic groups in the region. We consider the situation residents of the province during the war.